PENGARUH KUALITAS PELAYANAN DAN LOKASI AGEN TERHADAP LOYALITAS PELANGGAN PO. ROSALIA INDAH DENGAN HARGA SEBAGAI VARIABEL MODERASI - Nur Rohmat Sumarno Dwi Saputra (Universitas Slamet Riyadi, 2015)
The purpose of this study is: To analyze the significance of the effect of quality of service, location and price agent on customer loyalty PO. Rosalia Indah in Palur Karanganyar. To analyze the moderating effect of price on the influence of service quality and customer loyalty agent locations PO. Rosalia Indah in Palur Karanganyar. In conclusion: There was a significant effect of service quality on customer loyalty PO. Rosalia Indah in Palur Karanganyar. There was a significant influence on customer loyalty agent locations PO. Rosalia Indah in Palur Karanganyar. There was a significant influence on customer loyalty PO price. Rosalia Indah in Palur Karanganyar. Price does not moderate the impact of service quality on customer loyalty PO. Rosalia Indah in Palur Karanganyar. The results of the analysis we concluded that the price does not moderate effect on customer loyalty agent locations PO. Rosalia Indah in Palur Karanganyar. Keywords: quality of service, agent location, price and customer loyalty